2005
DOI: 10.1097/01.rhu.0000152150.01274.1b
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pulmonary Embolism Despite Inferior Vena Cava Filter Placement in Patients With the Antiphospholipid Syndrome

Abstract: In patients at risk for pulmonary emboli, consideration is often given to placement of an inferior vena cava (IVC) filter to prevent propagation of a distal thrombus. However, long-term benefits remain controversial, and deep venous thrombosis and IVC thrombosis may result from the procedure itself. Whether a filter if beneficial or even detrimental in patients with the antiphospholipid syndrome (APS) is unclear. We reviewed clinical outcomes in 2 patients who had IVC filter placement years before the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, there is a substantial percentage of non‐cancer patients for whom no specific therapy has proved to be superior. Some patients were found to have antiphospholipid antibodies, and would probably benefit from AVK therapy with a higher target of INR (Cherian & Gertner, 2005). Finally, for those who had a sub‐therapeutical INR at recurrence the best therapeutical approach would probably consist of a more accurate dose of AVK (Hull et al , 1982).…”
Section: Clinical Characteristics Treatment Details and Outcome Of mentioning
confidence: 99%
“…However, there is a substantial percentage of non‐cancer patients for whom no specific therapy has proved to be superior. Some patients were found to have antiphospholipid antibodies, and would probably benefit from AVK therapy with a higher target of INR (Cherian & Gertner, 2005). Finally, for those who had a sub‐therapeutical INR at recurrence the best therapeutical approach would probably consist of a more accurate dose of AVK (Hull et al , 1982).…”
Section: Clinical Characteristics Treatment Details and Outcome Of mentioning
confidence: 99%
“…In clinical situations where anticoagulation is not possible or not advisable, consideration is often given for the placement of an IVC filter to prevent propagation of clots. Limited case reports on the use of permanent filters suggested that clot formation can still occur proximal and distal to the filter and recurrent pulmonary emboli may still be seen (6,11). Cherian et al found clots on the proximal side of the filter (6).…”
Section: Discussionmentioning
confidence: 99%
“…However long-term benefits of filters remain controversial. In particular, in APS, recurrent pulmonary emboli and thrombus proximal and distal to the IVC filter have been described in patients with permanent filters (6). Experts recommend avoiding IVC filters in the acute APS setting, as these devices can be associated with a variety of adverse events, including IVC thrombosis and pulmonary embolus (PE) (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary embolism (PE) may be fatal in as many as 25% of patients1; IVC filter placement should be considered in such clinical situation. Despite their widespread use, long-term benefits of this intraluminal device remain controversial, particularly in complex cases such as patients with prothrombotic disorders as antiphospholipid antibody syndrome (APS) 2. We herein present the case of a young man with known history of APS and IVC filter placement in a retrohepatic position, who developed a chronic occlusion in the IVC and progressed to Budd-Chiari and post-thrombotic syndromes.…”
Section: Introductionmentioning
confidence: 99%